THE EFFECT OF TREFFINGER, LAPS-HEURISTIC MODELS, AND MOTIVATION ON STUDENTS’ WRITING ACHIEVEMENT - hasrul fahmi fahmi; Muhammad Nasir (Yayasan Hurriah, Banda Aceh, 2023)
This research was conducted with Quantitave research aimed to find out the students’ writing achievement taught by using Treffingers’ Learning Model and LAPS Heuristic Model and also to find out the students’ writing achievement with high and low motivation. The method of this research used was experimental research with factorial design 2x2. The sample of this study was XI IPA of SMA Negeri 1 Kota Lhokseumawe, which consisted of 36 students XI IPA, the sample was applied by random sampling technique. The instruments of this study were obtained by writing test and questionnaire sheet. The summary of post-test data description in each group of learning model showed in statistical is Treffingers’ Learning Model = 17.50 and LAPS Heuristic = 16.03. So, Treffingers’ Learning Model (17.50) > (16.03) LAPS Heuristic Model. Then, the data were analyzed by using ANOVA test at the level of significant ? = 0,05. Based on the data analysis, the findings proved that the students’ writing achievement taught by using Treffingers’ Learning Model was higher than that taught by using LAPS Heuristic Model, with Fobs (20.13) > Ftab (3.13).